The Muselmann at the Water Cooler - Pfefferkorn, Eli (Reference Library of Jewish Intellectual History, 2011)
"A survivor of concentration camps and the Death March, Eli Pfefferkorn looks back on his Holocaust and post-Holocaust experiences to compare patterns of human behavior in extremis with those of ordinary life. What he finds is that the concentration camp Muselmann, who has lost his hunger for life and is thus shunned by his fellow inmates on the soup line, bears an eerie resemblance to an officeemployee who has fallen from grace and whose coworkers avoid spending time with him at the water cooler. Though the circumstances are unfathomably far apart, the human response to their situations is triggered by self-preservation rather than by calculated evil. By juxtaposing these two separate worlds, Pfefferkorn demonstrates that ultimately the human condition has not changed significantly since Cain slew Abel and the Athenians sentenced Socrates."